Eh -Sayyeh, Jordanien: Die Aufarbeitung der Sondierungen 2013–2015: Die lithischen Kleinfunde - Rokitta-Krumnow, Dörte (e-Forschungsberichte des DAI, 2023)
The site of eh-Sayyeh is one of the most important Neolithic settlements in northern Jordan and was 2013–2015 subject of extensive soundings. The main objective was the study of the transition between the early and late Neolithic period at the end of the 8th / beginning of the 7th century BC. By evaluating the lithic material, simplified production techniques could be demonstrated, which were applied mainly at household level. The manufacture of special types of tools, for which particular knowledge is required, is comparatively rare. However, the high number of borers in the tool kit indicates a certain specialisation in the tool production at the site.